AHNA: Adaptive representation learning for attributed heterogeneous networks. Issue 2 (15th September 2021) - Shu, Lin; Chen, Chuan; Xing, Xingxing; Liao, Xiangke; Zheng, Zibin
Abstract: Meta‐path‐based random walk strategy has attracted tremendous attention in heterogeneous network representation, which can capture network semantics with heterogeneous neighborhoods of nodes. Despite the success of meta‐path‐based random walk strategy in plain heterogeneous networks which contain no attributes, it remains unexplored how meta‐path‐based random walk strategy could be utilized on attributed heterogeneous networks to simultaneously capture structural heterogeneity and attribute proximity. Moreover, the importance of node attributes and structural relations generally varies across data sets, thus requiring careful considerations when they are incorporated into representations. To tackle these problems, we propose a novel method, A ttributed H eterogeneous N etwork embedding based on A ggregate‐path (AHNA), which generates aggregate‐path‐based random walks on attributed heterogeneous networks and adaptively fuses topological structures and node attributes based on the learned importance. Specifically, AHNA first converts node attributes to additional links in the network to deal with the heterogeneity of structures and attributes, which is followed by an adaptive random walk strategy to strike the importance balance between node attributes and topological structures, thereby generating high‐quality representations. Extensive experiments are conducted on three real‐world data sets, where AHNA outperforms state‐of‐the‐art approaches by up to 22.7%, 2.6%, and 2.3% on link prediction, community detection, and node classification, respectively. Moreover, our qualitative analysis indicates that AHNA can capture different balances of topological structures and node attributes on various data sets and thus boost the quality of node representations.